THE DEVELOPMENT OF MORAL AND RELIGIOUS VALUES IN OVERCOMING THE TEENAGER NAUGHTINESS AT THE SENIOR HIGH SCHOOL (SMA) OF MUHAMMADIYAH 18 MEDAN - Syamsu Nahar (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
The purpose of this research is to reveal Teenager Naughtiness that occurs in SMA Muhammadiyah 18 Medan and the efforts of teachers to overcome it through the development of moral and religious values. This research is a qualitative research, with a case study approach at SMA Muhammadiyah 18 Medan. While the data collection method is in the form of interviews which are then analyzed using the data analysis model of Milles and Huberman. This research found the results of the study that: the type of Teenager Naughtiness in SMA Muhammadiyah 18 Medan was delinquency in the mild category. The forms of delinquency that occur are as follows: truancy, talking alone or busy during class hours, running from school during class hours, uniforms not as specified, smoking, not doing homework, not wearing belts and socks , Take lessons in other classes, cheating and dating. In anticipating and reducing the level of Teenager Naughtiness, SMA Muhammadiyah 18 Medan develops moral and religious values which are carried out in schools with religious activities. These activities are as follows: Praying in congregation, internalizing the value of Aqidah, understanding the value of sharia, and applying the values of Morals / character. Keywords: Moral values, religion, Teenager Naughtiness